2022
DOI: 10.1186/s12906-022-03705-y
|View full text |Cite
|
Sign up to set email alerts
|

Edible algae (Ecklonia cava) bioprocessed with mycelia of shiitake (Lentinula edodes) mushrooms in liquid culture and its isolated fractions protect mice against allergic asthma

Abstract: Background Ecklonia cava is an edible marine brown alga harvested from the ocean that is widely consumed in Asian countries as a health-promoting medicinal food The objective of the present study is to evaluate the anti-asthma mechanism of a new functional food produced by bioprocessing edible algae Ecklonia cava and shiitake Lentinula edodes mushroom mycelia and isolated fractions. Methods We used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…These included the reduction of elevated T-helper cell Th1 cytokine production to near normal levels, reduced expression of inflammatory mediators, reduced immunoglobulin production related to the Th1 and Th2 immune reaction, reduced elevated Treg IL-10 cytokine formation to near normal levels, reduced number of lymphocytes in bronchoalveolar lavage fluid (BALF), suppression of lung airway inflammation, and a protective effect on the morphology of lung tissues against inflam-K. S. Kwon et al DOI: 10.4236/fns.2023.144023 343 Food and Nutrition Sciences matory cell infiltration. The second study on the anti-asthma effect of the edible Ecklonia cava alga bioprocessed with mushroom mycelia showed similar beneficial molecular, cellular, and histological results [1]. Black rice bran that has been bioprocessed through fermentation with mushroom contains polysaccharides with reported physiological, health-promoting activities including the inhibition of infections by the foodborne pathogen Salmonella Typhimurium in mice [8] and the inhibition of lipopolysaccharide (LPS)-induced endotoxemia in mice [9] via the activation of the Th1 immune response in vivo.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…These included the reduction of elevated T-helper cell Th1 cytokine production to near normal levels, reduced expression of inflammatory mediators, reduced immunoglobulin production related to the Th1 and Th2 immune reaction, reduced elevated Treg IL-10 cytokine formation to near normal levels, reduced number of lymphocytes in bronchoalveolar lavage fluid (BALF), suppression of lung airway inflammation, and a protective effect on the morphology of lung tissues against inflam-K. S. Kwon et al DOI: 10.4236/fns.2023.144023 343 Food and Nutrition Sciences matory cell infiltration. The second study on the anti-asthma effect of the edible Ecklonia cava alga bioprocessed with mushroom mycelia showed similar beneficial molecular, cellular, and histological results [1]. Black rice bran that has been bioprocessed through fermentation with mushroom contains polysaccharides with reported physiological, health-promoting activities including the inhibition of infections by the foodborne pathogen Salmonella Typhimurium in mice [8] and the inhibition of lipopolysaccharide (LPS)-induced endotoxemia in mice [9] via the activation of the Th1 immune response in vivo.…”
Section: Introductionmentioning
confidence: 84%
“…Asthma is a lung disease characterized by chronic inflammation of airwayhypersensitivity mucus overproduction, airway remodeling, and airway narrowing that affects more than 300 million people worldwide and an estimated 7 million children in the United States. Allergic asthma, also known as severe asthma (SA), is an inflammatory incurable disease of the lungs and associated airways characterized by the infiltration of immune cells that is difficult to treat and manage [1] [2] [3]. Multiple factors, including genetics, air pollution, smoking, obesity, and consumption of ultra-processed food, are reported to contribute to the cause (etiology) of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [1] obtained a new functional food by bioprocessing (fermenting) E. cava with shiitake mushroom mycelia that protected mice against ovalbumin-induced allergic asthma. The new functional food also reversed the thickening of the airway wall and infiltration of bronchial and blood vessels and inflammatory cells.…”
Section: Colored Corn Floursmentioning
confidence: 99%
“…As part of efforts to create new functional foods that have the potential to ameliorate and treat human diseases, we reported that edible algae (Ecklonia cava) bioprocessed (fermented) in culture with shiitake mushroom mycelia was effective in neutralizing multiple biomarkers associated with allergic asthma in mice [1]. We also published a series of studies on the preparation of experimental, mostly gluten-free, flatbreads with other health benefits, as well as with a low content of the heat-induced toxin acrylamide formed during the baking process [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, algal species generating these materials can be revalorized since many of them are efficient β-glucan producers and these polysaccharides can be extracted from algal biomass or synthesized in controlled cultures of algal species [ 25 , 26 ]. Moreover, algal wastes can serve as substrates to cultivate other β-glucan producers such as mushrooms or yeasts, since they can utilize algal components for their nutrition [ 98 ].…”
Section: Conclusion Current Limitations and Future Perspectivesmentioning
confidence: 99%